(untitled) (Sustainability in Debate, 2019)
Reducing Deforestation and Forest Degradation (Redd) is a legal instrument created by the United Nations to prevent deforestation of the remaining native forests. The enforcement of safeguards that aim to protect communities receiving conservation projects is necessary to attain its full effectiveness. Pernambuco state defined the instrument through its Act nº 15.809/2016, outlining its own implementation criteria, in the absence of federal regulation. The state interest in the effectiveness is due to the intense process of degradation of its predominant biome: Caatinga. The biome has only 50% of its native vegetation cover. Thus, the study examines the proposed safeguards for Redd implementation in the Caatinga of Pernambuco. For this purpose, the safeguards were examined following the Redd Safeguard Spectrum Framework (RSS Framework) methodology. The results demonstrate that the defined safeguards are largely abstract, based on general principles, making their implementation and monitoring difficult.